Tafsir Bi-Ra'yi; Hukum dan Kedudukannya dalam Syariat Islam - Muhammad Arif; Dwi Sukmanila Sayska (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
In general, the interpretation of the Quran is divided into to methods; tafsir bil-ma'tsur (based on history) and tafsir bi ar-ra'yi (rational based). The validity of the bil-ma'tsur interpretation method is beyond doubt because the interpretation was quoted directly from the bearer of the message of the Prophet Muhammad, peace and blessings of Allah be upon him, as well as from his students, the Companions and the generation after that, namely the Tabiin. However, with regard to Tafsir bi-ra'yi, the scholars have different opinions about it. Some forbid it and some allow it. However, after studying it more deeply, it turns out that these differences are only lafzhi (formality) because both of them agree that it is haram to interpret the al-Qur’an with opinion (ra'yu) alone. As for interpreting the al-Qur’an based on knowledge, that is permissible. Of course, the science referred to here is sharia science such as ulumul Qurán, hadith, fiqh, ushul fiqh, arabic and so on so that the interpretation does not deviate from the values ​​that are standard in the Islamic religion. For this reason the Ulama established several rules and regulations for interpreting the al-Qur’an with reason (logic). The aim of this research is to thoroughly examine the position of bi-ra'yi interpretation in Islam by finding evidence from the al-Quran, hadith and the practices of the Salaf. This study uses qualitative methods with data collection techniques in the form of descriptive analysis and literature study. The results of the study found that interpreting the al-Quran should not be based solely on opinion (ra'yu). Bi-Ra'yi interpretation can only be accepted if it is supported by Sharia arguments, namely the al-Quran, Hadith and the opinions of the salaf scholars.